Pengabdian Masyarakat Melalui Kegiatan Penyuluhan Kesehatan Terhadap Tingkat Pengetahuan Tentang Penyakit HIV/Aids di SMAN 1 Baturaden - Galih Samodra; Siti Setianingsih; Barlian Kristanto; Reina Melani (LPPM Universitas Harapan Bangsa Purwokerto, 2023)
HIV/AIDS is a health problem in the world, including in Indonesia. he number of HIV/AIDS cases continues to increase from year to year. Adolescents are included in a group that is vulnerable to exposure to HIV/AIDS. As an effort to prevent and transmit HIV / AIDS can be done through health promotion. This activity aims to provide health promotion through outreach activities about HIV/AIDS to students at SMAN 1 Baturraden. The method used is using pretest and posttest. The results of community service activities showed an increase in knowledge about HIV/AIDS as seen from the increase in the score obtained. The conclusion of this activity is that counseling activities are easily accepted and increase knowledge about HIV/AIDS for students of SMAN 1 Baturaden.